Levocarnitine supplementation for management of hypertriglyceridemia in patients receiving parenteral nutrition. (16th September 2021) - Grucz, Traci M.; Crow, Jessica; Sugrue, David; Davis, Stephanie; Gager, Erin; Beattie, Jessica; Shermock, Kenneth M.; Jarrell, Andrew S.
Abstract: Background: Levocarnitine deficiency has been observed in patients receiving parenteral nutrition (PN) and can cause or worsen hypertriglyceridemia. The objective was to characterize use of levocarnitine supplementation in PN and evaluate its effect on triglyceride levels in hospitalized adults. Methods: This retrospective, single‐center study included patients with triglyceride levels ≥175 mg/dl while receiving PN who had a subsequent reduction in lipid injectable emulsion dose. A piecewise linear regression was used to evaluate trends in triglyceride levels before and after the intervention, defined as initiation of levocarnitine in PN for the levocarnitine group, or reduction in lipid injectable emulsion alone for the control group. Results: Two hundred sixty‐one patients who received PN had an elevated triglyceride level and lipid injectable emulsion dose reduction, of which 97 (37.2%) received levocarnitine in PN. The median (IQR) levocarnitine dose added to PN was 8.0 (5.7–9.9) mg/kg. Triglyceride levels at 30 days post‐intervention did not differ between groups (125 vs 176 mg/dl, P = .345). The addition of levocarnitine to PN was associated with a significantly greater rate of reduction in triglyceride levels pre‐intervention to post‐intervention compared with a reduction in lipid injectable emulsion alone (–11 vs –3 mg/dl per day; 95% CI, –15 to –2; P = .012). Conclusion: In hospitalized adults with hypertriglyceridemia who had a lipid injectable emulsion dose reduction, the addition of levocarnitine in PN was not associated with a difference in triglyceride levels at 30 days; however, a greater rate of improvement in pre‐intervention to post‐intervention triglyceride levels was observed.